The Oxford handbook of film music studies - Neumeyer, David (Oxford University Press, 2014)
This book charts the interdisciplinary activity around music in visual media, addressing the primary areas of inquiry: history, genre and medium, analysis and criticism, and interpretation. Part I cover the range most broadly, from the relations of music and the soundtrack to opera and film, textual representation of film sound, film music as studied by cognitive scientists, and Hanns Eisler's work as film composer and co-author of the foundational text Composing for the Films. Part II addresses genre and medium with chapters focusing on cartoons and animated films, the film musical, music in arcade and early video games, and the interplay of film, music, and recording over the past half century. Part III offer case studies in interpretation along with extended critical surveys of theoretical models of gender, sexuality, and subjectivity as they impinge on music and sound. Part IV is on analysis of systematically models harmonies used in recent films, issues of music and film temporality, and an analysis focuses on television. Part V covers topics including musical antecedents in nineteenth-century theater, the complex issues in sychronization of music in performance of early silent films, international practices in early film exhibition, and the symphony orchestra in film.